Anthropometric Measurements of the hand length and their correlation with the Stature of Bengali adult Muslim females (Bangladesh Journal of Anatomy, 2009)
Context: Stature or body height is one of the most important and useful anthropometric parameter that determine the physical identity of an individual. The study was done to estimate stature from the hand length on one hundred and fifty Bengali adult Muslim females. Study design: descriptive cross sectional study. Place of Study: department of Anatomy, BSMMU, Dhaka. Material: One hundred and fifty Bengali adult Muslim female was collected from BSMMU & some urban region of Dhaka. Method: Measurement of stature and hand length of right and left side was taken with a standard anthropometer and a slide caliper respectively. Result: The present study showed significant (p